Middleware Architecture - Ajana El Khaddar, Mehdia (IntechOpen, 2021)
Middleware refers to the intermediate software layer that bridges the gap between the heterogeneous hardware platforms and the backend applications requirements. It allows providing common services and programming abstractions and hiding the low-level management of the connected hardware. With the recent advances in distributed systems and enabling technologies, such as RFID, WSNs, IoT, IoE, cloud computing, context-aware pervasive computing, ubiquitous computing, etc., middleware design and development has become a necessity, taking increasing importance. This book provides a comprehensive overview of the different design patterns and reference models used in middleware architectures in general, followed by a description of specific middleware architectures dedicated to the use of the different emerging technologies, such as IoT, cloud computing, IEEE 802.11, etc. This book intends therefore to bring together in one place up-to-date contributions and remaining challenges in this fast-moving research area for the benefit of middleware systems' designers and applications developers.